Comparative epigenomics in distantly related teleost species identifies conserved cis-regulatory nodes active during the vertebrate phylotypic period - Tena, Juan J.; González-Aguilera, Cristina; Fernández-Miñán, Ana; Vázquez-Marín, Javier; Parra-Acero, Helena; Cross, Joe W.; Rigby, Peter W.J.; Carvajal, Jaime J.; Wittbrodt, Joachim; Gómez-Skarmeta, José L.; Martínez-Morales, Juan R.

(untitled) (Genome Research, 2014)
The complex relationship between ontogeny and phylogeny has been the subject of attention and controversy since von Baer’s formulations in the 19th century. The classic concept that embryogenesis progresses from clade general features to species-specific characters has often been revisited. It has become accepted that embryos from a clade show maximum morphological similarity at the so-called phylotypic period (i.e., during mid-embryogenesis). According to the hourglass model, body plan conservation would depend on constrained molecular mechanisms operating at this period. More recently, comparative transcriptomic analyses have provided conclusive evidence that such molecular constraints exist. Examining cis-regulatory architecture during the phylotypic period is essential to understand the evolutionary source of body plan stability. Here we compare transcriptomes and key epigenetic marks (H3K4me3 and H3K27ac) from medaka (Oryzias latipes) and zebrafish (Danio rerio), two distantly related teleosts separated by an evolutionary distance of 115–200 Myr. We show that comparison of transcriptome profiles correlates with anatomical similarities and heterochronies observed at the phylotypic stage. Through comparative epigenomics, we uncover a pool of conserved regulatory regions (≈700), which are active during the vertebrate phylotypic period in both species. Moreover, we show that their neighboring genes encode mainly transcription factors with fundamental roles in tissue specification. We postulate that these regulatory regions, active in both teleost genomes, represent key constrained nodes of the gene networks that sustain the vertebrate body plan.